Ulvan based materials doped with lithium sulfate salts as solid biopolymer electrolytes for energy storage applications - Gonzales, K.N.; Torres, F.G.; Sanchís, M.J.; Carsí, M. (Elsevier, 2024)
The conversion of algae biomass into high-value technological materials can promote the utilization of green algae and mitigate issues such as green tides and biofouling. This paper reports, for the first time, the utilization of ulvan in the production of solid biopolymer electrolytes (SBEs) doped with lithium sulfate salts. Ulvan were obtained from the green algae Ulva nematoidea using two different processing methods: hot water extraction and alkaline extraction. Hot water extraction enables the extraction of ulvan chains with a high molecular weight. In contrast, alkaline extraction produces a heterogeneous molecular weight distribution with Mw values of 730 kDa, 339 kDa, and 380 kDa. Frequency-dependent conductivity plots showed that SBEs made from ulvan extracted using the alkaline route featured higher conductivity than those SBEs made from water-extracted ulvan. The highest conductivity was obtained with ulvan extracted using the alkaline procedure, measuring 1.73 × 10−5 S/cm (tested at 10 MHz and 80 °C). The open conformation and low molecular weight of the ulvan extracted using the alkaline route would promote the segmental movement of ulvan chains and the mobility of Li+ ions. The results showed that ulvan can be used to produce solid-state electrolytes (SBEs) doped with Li-ion salt. The extraction procedure, Li-ion salt concentration, temperature, and frequency are essential variables that determine the conductivity of SBEs.
Keywords: Solid state electrolytes; Marine algae; Ionic conductivity; https://purl.org/pe-repo/ocde/ford#2.05.02